2017
DOI: 10.1186/s12888-017-1222-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of user experience of an objective test (QbTest) to aid ADHD assessment and medication management: a multi-methods approach

Abstract: BackgroundThe diagnosis and monitoring of Attention deficit hyperactivity disorder (ADHD) typically relies on subjective reports and observations. Objective continuous performance tests (CPTs) have been incorporated into some services to support clinical decision making. However, the feasibility and acceptability of adding such a test into routine practice is unknown. The study aimed to investigate the feasibility and acceptability of adding an objective computerised test to the routine assessment and monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…13,14 The Quantified behavioral Test (QbTest) is a CPT with a motion tracking system that measures the three symptom domains of ADHD: impulsivity, inattention, and hyperactivity. 13,14 The Quantified behavioral Test (QbTest) is a CPT with a motion tracking system that measures the three symptom domains of ADHD: impulsivity, inattention, and hyperactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The Quantified behavioral Test (QbTest) is a CPT with a motion tracking system that measures the three symptom domains of ADHD: impulsivity, inattention, and hyperactivity. 13,14 The Quantified behavioral Test (QbTest) is a CPT with a motion tracking system that measures the three symptom domains of ADHD: impulsivity, inattention, and hyperactivity.…”
mentioning
confidence: 99%
“…Various continuous performance tests (CPTs) are available to obtain objective measures of ADHD symptom severity, and these measures have been shown to facilitate the diagnostic assessment for ADHD and the evaluation of stimulant medication efficacy. 13,14 The Quantified behavioral Test (QbTest) is a CPT with a motion tracking system that measures the three symptom domains of ADHD: impulsivity, inattention, and hyperactivity. 15 Previous research has shown that the QbTest can be used to differentiate between patients with ADHD and controls in both children and adults.…”
mentioning
confidence: 99%
“…A final point to consider is that our qualitative interviews were only conducted with parents as children were unwilling to participate or deemed too young by their parents. Although this is common with this young sample [40], we will work with key stakeholders to refine our methods for gathering insight into the experiences of young people.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although comparatively less researched than its use for diagnosis, qualitative findings from a recent randomised controlled trial (RCT) indicate the potential for QbTest to aid medication management [21,22]. Clinician interviews have identified that the QbTest is useful in supporting their confidence in starting medication, choosing suitable titration schedules, communicating to families/schools about medication efficacy, and promoting medication adherence [21]. As well as being valued by clinicians, QbTest has been shown to be efficacious as a tool to assess symptom change as a result of medication.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the QbTest in the community looks promising 34. However, there are a number of unknowns in relation to its use in the CYPSE.…”
Section: Introductionmentioning
confidence: 99%